OC-110 Single center experience of groove pancreatitis. (28th May 2012) - Marangoni, G; Dickinson, K; Bokhari, S; Hakeem, A; Hamady, Z; Storey, R; Morris-Stiff, G; Smith, A M
Abstract : Introduction: Groove pancreatitis (GP) is a form of chronic segmental pancreatitis. Due to increased awareness of the condition, a greater number of cases have been reported in recent years. Clinical symptoms are heterogeneous, with abdominal pain and gastric outlet obstruction considered the most common, and can mimic pancreatic adenocarcinoma. Most of the published literature is represented by small series. Aim of the study is to describe our experience in the management of this condition. Methods: From January 2005 to December 2011, 47 patients with GP were treated in our Unit. 33 males (M:F=2.3:1); mean age was 50 (31–84), average number of hospital admissions was 4 (0–20), mean hospital stay was 10 days (1–82). Eight patients needed HDU/ICU support. Aetiology was alcohol in 41 (87%) and 13 were abstinent for more than 6 months at last follow-up. Amylase was elevated (3xN) on admission in 22. The most common feature was abdominal pain (n=40, 85%) and 50% (n=20) required daily use of opioids. Gastric outlet obstruction (n=7), jaundice (n=11) and acute renal failure (n=5) were less frequent. Exocrine insufficiency was present in 23 (49%). 13 had a dilated pancreatic duct (>5 mm) and 6 developed portal hypertension. Median follow-up was 34 months. Results: There were five deaths, one due to GP. 29 patients were treated conservatively; 11 required enteral feeding. 4 had ERCP and biliary stenting, two of which subsequently underwent biliary reconstruction. One patient had a pancreatic stent and then a Berne's procedure. Endoscopic drainage for pseudocyst (n=2), cholecystectomy (n=6) for sludge/stones, gastric bypass (n=3), Puestow procedure (n=1), Whipple's operation (n=4, two of which later required thoracoscopic splanchnicectomy—TS), TS (n=3), celiac plexus block (n=2) were the other interventions. Overall 28 (66%) patients are well with no or occasional use of analgesia, six patients still experience recurrent hospital admissions and 8 require regular use of analgesia but with improved symptoms. Conclusion: The majority of GP is caused by alcohol excess. GP can be effectively treated conservatively and pain (the most common symptom) managed with simple analgesia. Despite good support the majority remain addicted to alcohol. Radical surgery should be reserved for complex cases, as it is not always effective for pain relief, and when there is a diagnostic dilemma. Competing interests: None declared.